Rising Youth Unemployment During The Crisis How to Prevent Negative Long-term Consequences on a Generation? - Scarpetta, Stefano (OECD Publishing, 2010)
The global economic crisis has hit youth very hard. In the OECD area, the youth (15-24) unemployment rate rose by 6 percentage points in the two years to the end of 2009, to reach almost 19%. There are currently nearly 15 million youth unemployed in the OECD area, about four million more than at the end of 2007. And in countries like France and Italy, about one active youth in four is unemployed, while in Spain more than 40% of them are jobless
Keywords: Social Issues/Migration/Health